2003
DOI: 10.1002/adfm.200304266
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Low‐Loss Acrylate Polymers for Planar Light Circuits

Abstract: We have developed a materials system composed of liquid multifunctional fluorinated acrylate monomers that achieves very low absorption losses within both datacom and telecom wavelength ranges. Identified structure–property relationships have guided the design of polymers that are optimized with respect to their inherent materials properties and their ability to be processed into low‐loss optical waveguides. Together these co‐developed materials and processes combine to produce waveguides that have propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…A number of researchers and companies worldwide have been active in pursuing the investigation and development of polymer-based switches. [1][2][3][4][5][6][7][8][9][10][11][12][13] Recent improvements in the performance of the polymers used in the construction of such switches 14 has now led to a significant further advance in the performance of polymer-based thermo-optic switches, as is described herein.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A number of researchers and companies worldwide have been active in pursuing the investigation and development of polymer-based switches. [1][2][3][4][5][6][7][8][9][10][11][12][13] Recent improvements in the performance of the polymers used in the construction of such switches 14 has now led to a significant further advance in the performance of polymer-based thermo-optic switches, as is described herein.…”
Section: Introductionmentioning
confidence: 96%
“…We have developed a polymer waveguide materials system, which is based on multifunctional fluorinated acrylates, 14,15 and have recently extended this class of materials to more highly fluorinated polymers, which provide propagation losses less than about 0.1 dB/cm. Waveguides are fabricated from liquid acrylate monomer formulations by direct photolithography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies revealed that the approach of replacing hydrogen by halogen was generally easier and cheaper than that by deuterium [6]. Furthermore, halogenations, particularly fluorination, can offer interesting opportunities for the alteration of properties such as refractive index, hydrophobicity and thermal stability [3,7]. Therefore, a wide range of fluorinated polymers such as fluorinated polyacrylates [8], fluorinated polyimide [9], perfluorocyclobutane [10], fluorinated dendrimer and hyperbranched polymers [11], fluorinated poly(arylene ether)s [2,12], and polysiloxanes and inorganiceorganic hybrid polymers [13] have been synthesized and investigated for optical waveguide applications.…”
Section: Introductionmentioning
confidence: 98%
“…20, 21 We therefore synthesize UV-curable perfluoroether acrylates, such as UV-T with molecular structure shown in Fig. 20, 21 We therefore synthesize UV-curable perfluoroether acrylates, such as UV-T with molecular structure shown in Fig.…”
mentioning
confidence: 99%